Corpus-driven analysis of Pakistani newspaper editorials on COVID-19 discourse - Zahra, Tehseen; Abbas, Akhtar (Penerbit Universiti Kebangsaan Malaysia, 2022)
Cataclysmic changes by the gradual spread of COVID-19 have triggered the interest of scientists, scholars, academicians, and linguists in analyzing the discourse related to the spread of the pandemic. The descriptions made by all of these scholars not only contribute to language with linguistic innovations but also cause the emergence of human attitudes and behaviours. At the same time, the issues raised through the language used during the challenging time of such crises shape and reveal several human schemas of language, discourse, society, and culture. Several studies on past situations of diseases and calamities have provided critical analyses of these schemas of difficult times in human history. Discourses through various linguistic practices in this regard play a crucial role in shaping and demonstrating the schemas of the crisis hit societies. Media discourse, specifically, has hidden powers to exercise, identify and report various socio-cultural issues. The current study focuses on finding the themes of socio-cultural attitudes and behaviours that emerged from newspaper editorials published in Pakistani newspapers in February, March and April, 2020. To achieve this goal, the corpusdriven analysis of 198 newspaper editorials having 215,842 words was conducted. The study revealed various themes that prevailed in this pre-vaccination period of COVID-19 in Pakistan. The themes included the metaphoric use of the language such as battle, corps and frontline; racism while naming the virus as China virus or Hazara virus; conspiracy theories assumed to be associated with COVID-19 spread i.e. suspected involvement of Bill Gates and the Centers for Disease Control (CDC), US and World Health Organization (WHO); negligence on the part of people; and criticism on government for health facilities and implications of globalization. It is concluded, based on these findings, that media representation of prevaccination phase of COVID-19 in Pakistan is loaded with unhealthy discourse which could have been avoided in order to shape positive attitudes and behaviours of the masses.